Tectonic Regionalization of the Southern California Crust From Tomographic Cluster Analysis. Issue 11 (29th November 2019) - Eymold, William K.; Jordan, Thomas H.
Abstract: We map crustal regions in Southern California that have similar depth variations in seismic velocities by applying cluster analysis to 1.5 million P and S velocity profiles from the three‐dimensional tomographic model CVM‐S4.26. We use a K ‐means algorithm to partition the profiles into K sets that minimize the inter‐cluster variance. The regionalizations for K ≤ 10 generate a coherent sequence of structural refinements: each increment of K introduces a new region typically by partitioning a larger region into two smaller regions or by occupying a transition zone between two regions. The results for K ≤ 7 are insensitive to initialization and trimming of the model periphery; nearly identical results are obtained if the P and S velocity profiles are treated separately or jointly. The regions for K = 7 can be associated with major physiographic provinces and geologic areas with recognized tectonic affinities, including the Continental Borderland, Great Valley, Salton Trough, and Mojave Desert. The regionalization splits the Sierra Nevada and Peninsular Range batholiths into the western and eastern zones consistent with geological, geochemical, and potential‐field mapping. Three of the regions define a geographic domain comprising almost all of the upper crust derived from continental lithosphere. Well‐resolved regional boundaries coincide with major faults, topographic fronts, and/or geochemical transitions mapped at the surface. The consistent alignment of these surface features with deeper transitions in the crustal velocity profiles indicates that regional boundaries are typically narrow, high‐angle structures separating regions with characteristic crustal columns that reflect different compositions and tectonic histories. Key Points: Crustal regions in Southern California with similar seismic velocity profiles are mapped by applying cluster analysis to a tomographic model Regions correspond to major physiographic provinces and geologic areas with known tectonic affinities Region boundaries are typically narrow, high‐angle structures that separate regions with different crustal compositions and tectonic histories